A decomposition of the sources of incomplete cross-border transmission - Rebecca Hellerstein (Federal Reserve Bank of New York, 2006)
Despite its importance, the microeconomics of the international transmission of shocks is not well understood. The conventional wisdom is that relative price changes are the primary mechanism by which shocks are transmitted across borders. Yet traded-goods prices exhibit significant inertia in the face of shocks such as exchange rate changes. This paper uses a structural model to quantify the relative importance of manufacturers' and retailers' local-cost components and markup adjustments as sources of this incomplete transmission. The model is applied to a panel dataset of one industry with retail and wholesale prices for UPC (Universal Product Code)-level products. Markup adjustments by manufacturers and the retailer explain two-thirds of the incomplete transmission, and local-cost components account for the remaining one-third. Foreign manufacturers generally bear more of the cost (or reap more of the benefit) of an exchange-rate-induced marginal cost shock than do domestic consumers, domestic manufacturers, or the domestic retailer.
Keywords: F14; F3; F4; 330; cross-border transmission; exchange rates; pass-through; distribution margins; Wechselkurs; Schock; Spillover-Effekt; Exchange Rate Pass-Through; Einzelhandel; Großhandel; Preis; Bier; USA